OPTIMIZING WORKLOAD ALLOCATION IN A NETWORK OF HETEROGENEOUS COMPUTERS (Journal of Information and Communication Technology, 2011)
The allocation of workload to a network of computers is investigated. A new workload allocation model based on Generalized Exponential (GE) distribution is proposed for user-level performance measures. The criterion used for effective workload allocation is the one that minimizes the expected response time in systems to which jobs are routed. A closed-loop expression for workload arrival to minimize systems means queue length and response time are derived using the optimization technique. Results are presented with numerical examples and sensitivity analysis with respect to changes of total workload. Results are verified using the simulation technique.